2012
DOI: 10.1186/1471-2458-12-352
|View full text |Cite
|
Sign up to set email alerts
|

Eye movement responses to health messages on cigarette packages

Abstract: BackgroundWhile the majority of the health messages on cigarette packages contain threatening health information, previous studies indicate that risk information can trigger defensive reactions, especially when the information is self-relevant (i.e., smokers). Providing coping information, information that provides help for quitting smoking, might increase attention to health messages instead of triggering defensive reactions.MethodsEye-movement registration can detect attention preferences for different healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 55 publications
1
42
0
2
Order By: Relevance
“…Results showed that graphic warnings lowered participants' intentions to smoke in the future among those with a lifetime history of moderate smoking, and they increased the intention to quit smoking among those with a lifetime history of heavy smoking. These results are consistent with previous studies (Fong et al, 2009;Hammond, 2011;Kessels and Ruiter, 2012;Sobani et al, 2010) showing that pictorial health warnings on cigarette packages are more effective than text in informing consumers about the health risks associated with tobacco use and that they eventually lead to behavior change, as evidenced by an increase in the rate of smoking cessation.…”
Section: Introductionsupporting
confidence: 92%
“…Results showed that graphic warnings lowered participants' intentions to smoke in the future among those with a lifetime history of moderate smoking, and they increased the intention to quit smoking among those with a lifetime history of heavy smoking. These results are consistent with previous studies (Fong et al, 2009;Hammond, 2011;Kessels and Ruiter, 2012;Sobani et al, 2010) showing that pictorial health warnings on cigarette packages are more effective than text in informing consumers about the health risks associated with tobacco use and that they eventually lead to behavior change, as evidenced by an increase in the rate of smoking cessation.…”
Section: Introductionsupporting
confidence: 92%
“…In previous investigations conducted using eye-tracking technology, participants were given more time to view the packages (Strasser et al, 2012;Kessel & Ruiter, 2012;Piqueras-Fiszman et al, 2013;Clement et al, 2013). However, as this study analyses an impulse buy product, the research focused on finding out what a subject is able to view in his initial brief visual engagement with a product of these characteristics.…”
Section: Experiments Set-up and Completionmentioning
confidence: 99%
“…This technique seeks to find out which packaging elements capture user attention when they are carrying out a specific task, such as deciding how healthy a packaged product is. Other studies focus on examining stimulus-driven attention (Kessel & Ruiter, 2012;Strasser, Tang, Romer, Jepson, & Cappella, 2012). This technique studies the areas on a packaging that capture user attention when they do not have to carry out a specific task, observing stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…It is well documented that this most-at-risk group is also the one that resist antismoking messages the most, in the form of selective attention and perception (e.g., Hwang, 2010), defensive avoidance (e.g., Kessels & Ruiter, 2012), biased perception (e.g., Freeman et al, 2000), and psychological reactance (e.g., Erceg-Hurn & Steed, 2011). The main effect of smoker status confirmed this resistance from smokers: Nonsmokers found the antismoking messages to be most effective, while regular smokers found them to be the least effective (cf.…”
Section: Targeting Smokersmentioning
confidence: 99%